“Your Diet Defines Who You Are, Especially as a Man”: Masculinity in Online Media Focused on Healthy Eating for Men - Ruby Jelicich; Virginia Braun (American Journal of Men's Health, 2023)
In contexts marked by neoliberal ideology and a claimed “crisis” in men’s health, men are responsibilized to be/come healthy. Eating has long been a gendered practice in Western cultures, and recent cultural shifts have produced ways of eating that are both masculinized and (claimed) healthy. Online healthy eating advice, which encourages and supports men to eat healthily, is an important information source. However, such information draws on, reproduces, and/or disrupts existing meanings about men and eating. To understand contemporary representations of men and healthy eating, we examined 30 online media articles oriented specifically to this topic. Using reflexive thematic analysis from a social constructionist position, we developed two themes: A lad’s looks and lifestyle and Mind over matter: The masculine mindset. These themes together told an overarching story that healthy eating is effectively sold to men by drawing on traditional or hegemonic ideals of masculinity and effectively evoking access to an enhanced masculinity through healthy eating. While these representational practices may sell healthy eating to men, with likely positive health benefits, they also reinforce hegemonic ideals of masculinity which can be problematic from a health perspective.